High-temperature, high-pressure rheology of water-based muds. - Alderman,NJ; Gavignet,A; Guillot,D; Maitland,GC (1988)
This paper reports measurements of the rheology of a range of water based drilling muds at temperatures up to 130DEGREESC and pressures up to 1000 bar. The fluids were highly thixotropic, and decoupling of temperature/pressure effects from those due to time dependent structural changes was achieved by developing a sample preparation and handling procedure which ensured that all samples experienced identical shear histories prior to study in the rheometer. The observed behaviour of the fluids and its physical origins are discussed. A simple model allowing reliable extrapolation of surface measurements to downhole conditions for well circulated water based muds is presented.